Selective Methylation of NH-Containing Heterocycles and Sulfonamides Using N,N-Dimethylformamide Dimethylacetal Based on Calculated pKa Measurements - Fairley, Gary; Hall, Catherine; Greenwood, Ryan (Synlett, 2013)
The use of N,N-dimethylformamide dimethylacetal (DMF-DMA) as a suitable methylating agent for the methylation of NH-containing groups and heterocycles has been investigated. Use of ReactArray and calculated pKa measurements have allowed additional helpful information to be collated to determine optimum reaction conditions for a variety of substrates.
Keywords: methylation; N,N-dimethylformamide dimethylacetal; heterocycles; sulfonamides; pKa